ØªØ·Ø¨ÙŠÙ‚ Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…Ø®ØªÙ„Ø·( Blanded Learning)Ù„ØªØ±Ù‚ÙŠØ© ÙÙ‡Ù… Ø§Ù„Ø·Ø§Ù„Ø¨Ø§Øª Ø£Ø«Ù†Ø§Ø¡ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø¹Ø§Ù„ÙŠØ© "Ù…Ø¹Ù„Ù…Ø§Øª" Ø¬ÙˆÙƒÙŠØ±ØŒ Ø¬ÙˆÙ…Ø¨Ø§Ù†Ø¬ØŒ Ø¬Ø§ÙˆÙ‰ Ø§Ù„Ø´Ø±Ù‚ÙŠØ© - Eka Silvia Khumairah; Lailatul Qomariyah (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2021)
Blended learning is a relatively new concept in education in which teaching is delivered through a combination of online and traditional learning, which is practically performed by a teacher. The application of blended learning is a method that is implemented through both online and offline learning that Includes educational media or educational applications. This method can also help in learning during the COVID-19 pandemic, and this method can be a reference for implementing effective and effective learning in understanding students about learning, especially learning Arabic. The method of this qualitative research is more specifically directed towards the use of the case study method, that is, in-depth and detailed research on everything related to the research topic. Basically, the method of data collection is observation, interview and documentation. Data analysis steps include data reduction, data presentation, and conclusion.